Variables associated with disordered eating behaviors among freshman students from Mexico City - Concepción Díaz de León-Vázquez; José Alberto Rivera-Márquez; Letza Bojorquez-Chapela; Claudia Unikel-Santoncini (Instituto Nacional de Salud Pública, 2017)
Objective. To estimate the prevalence of disordered eating behaviors (DEB) and identify their associations with demographic and psychological variables among freshman students at a public university in Mexico City. Materials and methods. A sample of 892 subjects participated in the study. Bivariate and multinomial models were performed to determine associations between DEB and covariates. Results. Of those surveyed, 6.8% of the women and 4.1% of the men exhibited DEB (p<0.05). The variables increasing the risk of eating disorders (ED) for women were internalization of the aesthetic thin ideal (IATI), body mass index (BMI), self-esteem and physical activity, while for men they were IATI, drive for muscularity, and self-esteem. Conclusions. The frequency of DEB among women and men and the internalization of the thin ideal in both sexes suggest the possibility of a change in the precursor conditions for eating disorders, particularly for men, who exhibit increased risk of such behaviors.